A trajetória educacional de estudantes com indicadores de altas habilidades/superdotação - OLIVEIRA, Elaine Cristina Batista Borges de (2022)
In Brazil, the topic of High Skills/Giftedness is one of the areas of Special Education. This research seeks to discuss the topic of inclusion through the observation of the educational trajectory of students with indicators of high abilities/giftedness who showed early signs of giftedness and were participants in the Program of Assistance to Students with High Abilities/Giftedness (PAPCS) until the year 2018, when it was closed. The present investigation answers the following question: What are the impacts on the academic life trajectory of people with high skills/giftedness indicators after receiving care in a specialized care program? In this sense, we justify our research intentions through the descriptions of the families' reports, the analysis of their behaviors that indicate high skills/giftedness in elementary school, through an interview carried out in 2020. The objective is to describe and analyze their school development, after contacting the PAPCS. The research methodology uses a qualitative approach, through the semi-structured interview (ES) procedure to discuss a case study of three participants, between 13 and 16 years old in the course of their school life. The reflections are based on Renzulli's theory (1998, 2004) and on Bardin's (1977) content analysis, which were interpreted considering two stages: 1. Family voice; 2. Student voice with indicators of high abilities/giftedness. For the review of previous studies, the analyzes of the Capes Theses and Dissertations Bank were considered; consultation of data from institutions such as UMESP, UFSM, Scielo, Research Gate and face-to-face research at the UMESP Physical Library. We found that, even though family members recognize indicators of characteristics of high abilities/giftedness in their children’s behaviors, there are still difficulties to be overcome in terms of self-recognition and insertion in the school environment. However, it was possible to verify that all had support networks in the family environment, considering gifted behaviors. Specialized school educational assistance was ignored in two cases and one of them received support at school. Some different variables brought difficulties in the journey of each participant such as socioeconomic differences, engagement with the cause, school environments unfavorable to the development of potential. We conclude that the lack of appropriate and specialized care made it difficult for two students to go to school and generated difficulties in adapting to their school life. These omissions caused in the gifted student feelings of inadequacy in their social, family and school context. In this way, we observe that the family, the specialized educational service and the prepared school are crucial to contribute to the healthy and integral school trajectory of the gifted student.(AU)